ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT. BANK ACEH SYARIAH CABANG KUTACANE - Malahayati, Rina (Department of Accounting, Faculty of Economics & Business, 2020)
this study tries to uncover and analyze the practice of applying the principles of Good Corporate Governance at PT. Bank Aceh Syariah Kutacane Branch. The population of this study is Bank Aceh Syariah Kutacane Branch SouthEast Aceh Regency. The Observation of year is 2018. The data analysis technique used in this study is Reduction of data, Presentation of data and conclusion. The result of this research that the implementation of good corporate governance in PT. Bank Aceh Syariah branch of kutacane has been running and implementing wellness. Based on four principle namely Transparency, Accountability, Responsibility, and Fairness in accordance with the laws and the regulations implemented by Bank Indonesia.